A Causal Relationship Model of Factors Affecting the Quality of Work Life of Employees in Public Higher Education Institutions - อุดร, นาวี; ฉลากบาง, วัลนิกา; เพ็งสวัสดิ์, วาโร; เสถียรนพเก้า, พรเทพ (Ratchaphruek Journal, 2019)
The purposes of this research were to 1) develop causal relationship model of factors affecting the quality of work Life of employees in public higher education institutions 2) verify the developed of causal relationship model concordance of factors affecting the quality of work life of employees in public higher education institutions. The study was divided into 2 stages as follows. The first stage was to develop model by exploring relevant documents and researches and expert interview. Then content analysis was applied to analyze the data. The second stage was to verify of model concordance. The data was gathered by using questionnaire with 5-points scales. Its discrimination value was between 0.31 to 0.89 and its total reliability value was 0.98. The samples were 524 Employees in public higher education institutions, during academic year 2017. The data were analyzed to figure out frequency, percentage, mean, standard deviation, Pearson’s Product Moment Correlation Coefficient, and examination of goodness-of-fit indices between the model and the empirical data were conducted using statistical computer package. The study yielded the following results: 1) The causal relationship model of factors affecting the quality of work life of employees in public higher education institutions consisted of 5 factors as follows: organizational climate, job characteristic, job satisfaction, organizational commitment, and quality of work life, 2) The developed model has goodness-of-fit indices with the empirical data with the statistics as follows: Chi-square = 51.84, p-value = 1.00, df = 116, χ2/df = 0.45, RMSEA = 0.00, GFI = 0.99, AGFI = 0.98, Largest standardized residual = 1.96. The organizational climate, job characteristic, job satisfaction, and organizational commitment, all the factors could jointly explain 91 percent of quality of work life.